Cerebral Palsy: Risk Factors, Pathophysiology, Clinical Manifestations, Diagnosis, and Management - Damayanti, Ida Ayu Andara; Prawira, I Nyoman Dio Yudha; Andini, Syabila; Hanifah, Hanum Retno; Wiguna, I Made Danuarta; Wulandari, Baiq Nurhandini; Sabrina, Khansa Aulia; Khotimah, Andi Husnul; Wardana, Shira Putri; Rizqullah, Rifqi; Haikal, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Cerebral palsy is a non-progressive neuromotor disorder and the leading cause of motor disability in children worldwide, particularly in low- and middle-income countries. This study aims to examine the risk factors, pathophysiology, clinical manifestations, diagnosis, and management of cerebral palsy based on recent scientific literature. This article includes a systematic literature review using the PRISMA method and selected 15 articles that met the inclusion and exclusion criteria. The results of the systematic literature review were obtained risk factors for cerebral palsy include intrauterine infection, preeclampsia, premature birth, asphyxia, and hypoxic-ischemic encephalopathy and hyperbilirubinemia. These risk factors can disrupt neurogenesis and brain maturation, leading to structural and functional damage to the central nervous system. Clinical manifestations of cerebral palsy include impaired muscle tone, abnormal reflexes, and postural deformities, classified as spastic, dyskinetic, and ataxic, and assessed using the Gross Motor Function Classification System (GMFCS). The diagnosis of cerebral palsy is established through evaluation of the clinical history, neurological/motor examination, neuroimaging, and genetic testing. Cerebral palsy management aims to improve functionality, ability, and health in movement, cognition, social interaction, and independence. Non-pharmacological management focuses on physiotherapy and occupational therapy to improve motor skills, reduce spasticity, and support independence. The mainstay of pharmacotherapy in cerebral palsy management uses systemic medications that are symptom-based and directed at specific movement disorders.